Semantic Value in the Umayyad Contradictory Poetry in the Light of Cultural Criticism - نصّور أزدشير; عدنان أحمد (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
The structural formation of the language of contradictions carries meanings that emerged from the values that were employed in poetry. This is because poetry is the voice of society that conveys its conditions, news, days, and everything that revolves in the consciousness of poets; the sons of society. Hence, values appeared in the texts of contradictions clearly, whether they were of ignorant origin, Islamic origin, or Umayyad manifestation. The fields of literary criticism have shed light on the semantic values carried by contradictions, focusing on the aesthetics of generosity, chivalry, pride in lineage, loyalty and belonging, and glorifying the centrality of revenge. However, cultural criticism focuses on the underlying flaws that were hidden behind the cloak of these aesthetics, including acquisition, poetic hypocrisy, fluctuating lineage and loyalty, and the treachery and betrayal that revenge may entail. Therefore, contradictions, with their abundance, were a fertile material for tracing values, including literary aesthetics and cultural flaws. Keywords: Value, Contradictions, Criticism, Literary, Cultural.